(untitled) (Research, Society and Development, 2023)
Hydrogenated cardanol derivatives were evaluated as potentially active insecticides/repellent agents against insect pests such as Liriomyza sativae (Diptera: Agromyzidae) and Bemisia tabaci biotype B (Hemiptera: Aleyrodidae). Benzoylation, acetylation, and methylation were made on the hydrogenated cardanol aromatic ring to synthesize active ingredients with potential insecticide action. Nuclear magnetic resonance spectra (13C and 1H NMR) and infrared (IR) proposed the chemical elucidation of the products. The production of melon seedlings was made and each synthesized products, benzoylated 3-pentadecylphenol, acetylated 3-pentadecylphenol, and methylated 3-pentadecylphenol were applied to seedlings by glass sprayer. Phytotoxicity evaluations were carried out, noting that all the plants showed burnt leaves except for concentration of 1% which the leaves remained healthy look. The insecticidal efficacy as well as the repellent and dissuasive effects were evaluated by a completely randomized design (DIC) and a randomized complete block design (DBCA) with six treatments, five and four replicates respectively. The compounds derived from cardanol did not present insecticidal activity in DBCA for L. sativae; however, they had a noticeable effect on oviposition index (IPO). Ovicidal effect and nymphal mortality only were found for B. tabaci by methylated 3-pentadecylphenol and Mospilan® in terms of dissuasion and oviposition effects in the two bioassays evaluated and, methylated 3-pentadecyl showed a similar behavior as the effect of Abamectin® on the confinement test, with 53.5% - 65.4% repellence of adults, an important data to emphasize that the products synthesized from cardanol are promising in preventing the pests attack such as L. sativae and, B. tabaci.